A morphometric study on different shapes of pterion and its clinical significance - YUVARAJ.M; PUSHKARAN.J; SANKARAN P K; PRIYADARSHINI; GUNAPRIYA RAGHUNATH (International Journal of Pharma and Bio Sciences, 2017)
Pterion is a H- shaped sutural confluence seen in the Norma Lateralis of skull.It is the meeting point of four bones, the frontal, parietal, greater wing of sphenoid and the squamous part of temporal bone. The anterolateral fontanelle in the neonatal skulls close after 2-3 months to form the pterion Four types of pterion ( sphenoparietal, frontotemporal, stellate, epipteric) were defined by Murphy in 1956. It is commonly employed in surgical treatment of Tumours involving inferior aspects of frontal lobe, like olfactory meningiomas, oribital, retro-oribital sellar, chaismatic, subfrontal, prepontine areas, anterior circulation and basilar artery aneurysm. The knowledge regarding the various shapes and distances from different points to pterion is useful for treating number of pathologies in brain. So this is so useful for neurosurgeons, anatomists, anthropologist and forensic medicine.